2020
DOI: 10.33710/sduijes.701220
|View full text |Cite
|
Sign up to set email alerts
|

STEM Eğitimi ve Arduino Uygulamaları Hakkında Öğretmen Adaylarının Görüşleri

Abstract: In this journal, research articles which reflect the survey with the results and translations that can be considered as a high scientific quality, scientific observation and review articles are published. Teachers, students and scientists who conduct research to the field (e.g. articles on pure sciences or social sciences, mathematics and technology) and in relevant sections of field education (e.g. articles on science education, social science education, mathematics education and technology education) in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
0
3
0
1
Order By: Relevance
“…Similarly, many studies have stated that programming activities with Arduino tools improve understanding of the concepts (Ntourou et al, 2021) and overall performance (Omar, 2018). Furthermore, findings have reported that this new approach improves students' problem-solving (Wang et al, 2016), creativity (Cano, 2022;Kobsiripat, 2015), computational thinking (Juškevičienė et al, 2021;Ntourou et al 2021); algorithmic thinking (Sari et al, 2022), collaborative work (Alimisis and Kynigos, 2009), establishing a cause-effect relationship (Görgülü Arı and Meço, 2021), entrepreneurship (Sarı and Yazıcı, 2020), and coding skills (Alimisis and Kynigos, 2009). In addition, block-based coding has recently started to be used in the programming of Arduino hardware, instead of text-based coding.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…Similarly, many studies have stated that programming activities with Arduino tools improve understanding of the concepts (Ntourou et al, 2021) and overall performance (Omar, 2018). Furthermore, findings have reported that this new approach improves students' problem-solving (Wang et al, 2016), creativity (Cano, 2022;Kobsiripat, 2015), computational thinking (Juškevičienė et al, 2021;Ntourou et al 2021); algorithmic thinking (Sari et al, 2022), collaborative work (Alimisis and Kynigos, 2009), establishing a cause-effect relationship (Görgülü Arı and Meço, 2021), entrepreneurship (Sarı and Yazıcı, 2020), and coding skills (Alimisis and Kynigos, 2009). In addition, block-based coding has recently started to be used in the programming of Arduino hardware, instead of text-based coding.…”
mentioning
confidence: 93%
“…In line with this trend, many esteemed researchers have stated that the use of Arduino offers an ideal learning environment for STEM education (Eguchi, 2016;Hoffer, 2012). For instance, some researchers suggest that not only does the use of Arduino in STEM applications increase conceptual understanding (Demirer and Pabuçcu-Akış, 2023) and motivation among learners (Dönmez, 2017;Sarı and Yazıcı, 2020) but also enhances their perceptions of STEM careers (Kuo et al, 2019). For instance, Görgülü-Arı and Meço (2021) developed Arduino-supported STEM activities for 6th-grade students about human body systems lessons to improve their aptitude in cause-effect relationships.…”
mentioning
confidence: 99%
“…(2022), fizik öğretmen adaylarına uyguladığı çevrim içi TPAB-STEM uygulaması öncesi yeterli düzeydeki TPAB-STEM becerilerinin uygulama sonrası çok iyi düzeyde olduğunu belirtmiştir. Sarı ve Yazıcı (2020) fen bilgisi öğretmen adaylarının STEM eğitimi almalarının bu eğitime yönelik bilgi, beceri ve deneyim kazandırdığı sonucuna ulaşmış ve STEM eğitimi hakkında olumlu düşünceler geliştirdiklerini belirtmiştir. Değirmenci (2020), STEM eğitimine yönelik öğretmen öz yeterliliklerinin cinsiyete göre farklılaşmadığı, nitekim alınan STEM eğitimi sayısına göre anlamlı bir farklılaşma olduğu sonucuna ulaşmıştır.…”
Section: Introductionunclassified
“…A number of researchers in [13], [14], [15] consider possible forms of educational STEM projects in the field of electronics and device controlling that may be used for educational projects in robotics, based on the use of the Arduino platform. Boards with Atmel AVR microcontroller and some others are produced under the Arduino trademark.…”
Section: Introductionmentioning
confidence: 99%